Perceptions of Body-Worn Cameras: Findings from a Panel Survey of Two LAPD Divisions - Wooditch, Alese (American journal of criminal justice, 2020)
This paper examines results from two waves of officer surveys, administered before and after deployment of body-worn cameras (BWCs) in two divisions within the Los Angeles Police Department (LAPD). Officer surveys were administered in LAPD’s Mission and Newton divisions at two time points, pre-BWC deployment (August and September 2015; Wave I) and post-deployment (summer of 2016; Wave II). This fixed-sample survey contained 52 questions designed to measure officer perceptions of BWCs across a variety of domains. Questions were tailored to provide consistency across sites for comparison with other studies. Results varied by division, with Mission officers becoming more critical and Newton officers becoming slightly more supportive of BWCs over time. Similarities and differences in officer perceptions both between divisions and from pre- to post-deployment are discussed at length, as are the implications for policy and practice including obtaining organizational support and officer buy-in.